Location-Based Information Systems : Developing Real-Time Tracking Applications - Miguel A. Labrador; Alfredo J. Perez; Pedro M. Wightman (Chapman and Hall/CRC, 2011)
Drawing on the authors'more than six years of R&D in location-based information systems (LBIS) as well as their participation in defining the Java ME Location API 2.0, Location-Based Information Systems: Developing Real-Time Tracking Applications provides information and examples for creating real-time LBIS based on GPS-enabled cellular phones